Design and development of a third-person futuristic adventure game (B) - Pare, Ocampo Jessica Anne (2018)
This report looks into the developmental process of a video game. Before development, the elements that motivate video game play were identified: high-quality graphics, interesting game mechanics and compelling narratives. These elements served as the objectives for the project, ensuring that the game developed would be relevant. The different game development softwares, game engines, were compared and analysed to find the engine that was most suited to the project; the engine that would meet the objectives set. With the selected game engine, steps were taken to ensure that the project delivered the best possible graphics. Various techniques were employed in the creation of the materials for static meshes to ensure the quality of the graphics is maintained. In addition, the effect features offered by the selected game engine were fully utilised to add realism to the levels created. Two game mechanics: objective system and climbing system, were developed using the engine, adding more interesting ways in which a player interacts with a level.